The Effect Of Giving Chicken Dung In The Mushroom Media Composting Process Merang On Growth Characteristics And Results Of Straw Mushroom ( V Olvariella Volvaceae ) - Ahmad Suriadi; Rifky Haikal (Yayasan Hisnul Muslim Lombok, 2024)
Volvariella volvaceae (Bull. Ex. Fr), commonly known as straw mushroom, is the most recognized species among numerous tropical and subtropical mushroom species, particularly among the Southeast Asian community. The straw mushroom is also a source of several types of enzymes, particularly trypsin, which plays an important role in aiding the digestion process. Straw mushrooms can also be used as a protective food due to their complete B-complex vitamin content, including riboflavin, as well as having a fairly complete range of essential amino acids. The purpose of this research is to examine the effect of straw mushroom media containing chicken manure on the growth of straw mushrooms. (Volvariella volvacea). This research was conducted at the oyster mushroom cultivation facility of the Faculty of Agriculture at Nahdlatul Wathan University in Mataram. The implementation period started in August and ended in October 2023. This research uses a Completely Randomized Design (CRD) with a single treatment, namely the effect of chicken manure application on the composting process of straw mushroom media. The treatment is placed on 5 racks in a stacked manner. The treatments used were as follows: 300 kg of straw, 30 kg of rice bran, 25 kg of lime, and 50 kg of chicken manure. The application of chicken manure in the composting process of straw mushroom media significantly affected the time it took for the pinhead of the straw mushroom fruit body to appear; however, there were no significant differences in the parameters of the number of fruit bodies, diameter of the fruit bodies, length of the fruit bodies, and fresh mushroom media significantly affected the time it took for the pinhead of the straw mushroom fruit body to appear ; however, there were no significant differences in the parameters of the number of fruit bodies, diameter of the fruit bodies, length of the fruit bodies, and fresh weight of the straw mushrooms.